The Job Evaluation Program of the State Farm Insurance Companies Compared with those of Other Leading Insurance Companies as to Methods of Introducing and Content - Lanham, Elizabeth (Journal of Finance, 1953)
Elizabeth Lanham, The Job Evaluation Program of the State Farm Insurance Companies Compared with those of Other Leading Insurance Companies as to Methods of Introducing and Content, The Journal of Finance, Vol. 8, No. 1 (Mar., 1953), pp. 68-69